A study on the relationship between customer satisfaction towards service quality in a three-star hotels in Perlis / Nurul Labanihuda Abdull Rahman ... [et al.] - Abdull Rahman, Nurul Labanihuda; Samsul, Syaza Syahirah; Ibrahim Brian, Muhammad Shyazzwan; Idrus, Nurul Izzati (Universiti Teknologi MARA, Kedah, 2022)
The hotel industry has the central element in contributing income for Malaysia. This study aims to examine the relationship between the service quality dimension and customer satisfaction in the three-star hotels in Perlis. The conceptual model is based on the SERVQUAL model, and the dimensions used by this study are tangibility, reliability, responsiveness, assurance, and empathy. By investigating these factors, the study will identify the most significant factor contributing to customer satisfaction, especially in three-star hotels, Perlis. A total of 131 respondents who were the customers of Hotel Seri Malaysia Kangar had participated in the present study by completing a questionnaire on study skills. The findings found the tangibility, responsiveness, and empathy indicate a significant relationship with customer satisfaction. However, there is no significant relationship between reliability and assurance among customer satisfaction towards the hotel. This study contributes to the significant element that plays an essential role in improving the hotel service quality.